Identifying Distinct Risk Thresholds of Glycated Hemoglobin and Systolic Blood Pressure for Rapid Albuminuria Progression in Type 2 Diabetes From NHANES (1999–2018) - Xu, Jiahui; Xue, Yan; Chen, Qingguang; Han, Xu; Cai, Mengjie; Tian, Jing; Jin, Shenyi; Lu, Hao (Frontiers in Medicine, 2022)
Background: It is widely recognized that glycated hemoglobin (HbA1c) and systolic blood pressure (SBP) are two key risk factors of albuminuria and renal function impairment in patients with type 2 diabetes mellitus (T2DM). Our study aimed to identify the specific numerical relationship of albumin/creatinine ratio (ACR) with HbA1c and SBP among a large population of adults with T2DM. Method: A total of 8626 patients with T2DM were included in the data analysis from the National Health and Nutrition Examination Surveys (NHANES) (1999-2018). The multiple linear regressions were used to examine the associations of ACR with HbA1c and SBP. Generalized additive models with smooth functions were performed to identify the nonlinear relations between variables and interactions were also tested. Results: Significantly threshold effects were observed between ACR and HbA1c or SBP after multivariable adjustment, with the risk threshold values HbA1c = 6.4% and SBP = 127mmHg, respectively. Once above thresholds were exceeded, the lnACR increased dramatically with higher levels of HbA1c (β= 0.23, 95 CI%: 0.14, 0.32, P < 0.001) and SBP (β= 0.03, 95 CI%: 0.03, 0.04, P < 0.001). In addition, a higher risk of ACR progression was observed in central obesity participants with HbA1C ≥ 6.4 % or hyperuricemia participants with SBP ≥ 127mmHg among T2DM patients. Conclusions: We identified thresholds of HbA1c and SBP to stratify T2DM patients with rapid albuminuria progression. These might provide a clinical reference value for preventing and controlling diabetes kidney disease.